Cross (CLT) and diagonal (DLT) laminated timber as innovative ma-terial for beam elements - Bejtka, Ireneusz (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Lehrstuhl für Ingenieurholzbau und Baukonstruktionen, 2011)
Cross laminated timber (CLT) is a plate-like multi layer element with crosswise arrangement of lamellas. CLT could be used for long-span beams in particular with tensile stresses perpendicular to the beam axis. Within this work, CLT beams were optimised, resulting in diagonal orientated timber (DLT). Both CLT and DLT beams were tested in edgewise bending. Their load-carrying behaviour was studied using experimental results and finite element analysis.